The comparison of [ARCGIS] and [QGIS] software using geocoding method for postal code enhancement in mailing delivery / Syed Izzad Syamil Syed Mahdi - Syed Mahdi, Syed Izzad Syamil (2019)
Geocoding is the process of assigning location, basically in the form of x and y values (coordinates), to an address by comparing the descriptive location elements in the address to those present in the reference materials. Besides, the geocoding process is involving steps in translating an address entry. Postal code enhancement is not new in this world. Many countries for example United States, United Kingdom and France are always updating their postal code from time to time. Regardless until new, there is non-upgrading research being made to Malaysia's postcode system. The objectives of this study are to review the capabilities of geocoding in ArcGIS and QGIS and to compare both software in terms of completeness and positional accuracy. In geocoding process using ArcGIS reference data is needed. Data of road and proposed postcode are used as the reference data in this research. The geocoding analysis is done using a proposed postal code made for pilot study area, Kangar Perils, which this postal code is generated by using a specific coding model that made for Malaysia, The result of each geocoding method using by each software is determines and compared based on their match rates and accuracy. The result shows both software has equally capabilities in geoeoding.